International Students and Community Involvement in Tiffin, Ohio - Arnold, Julie; Crooks, Rachel; Moore, Joe (Journal of International Students, 2015)
Situated in northwest Ohio, Tiffin is a small community of 18,000 residents and is the proud home of two institutions of higher learning: Heidelberg University and Tiffin University. Over the last several years a unique collaboration has developed among the two universities and the community’s International Cultural Center (ICC). As most things do, this partnership began with a single idea and has blossomed into an evergrowing number of events and activities. Working closely together, these three entities have made concerted efforts to integrate the international student body into the greater Tiffin community. In doing so, the city has become “internationalized” in ways that have provided mutual benefits to the community and the international student population.